Individual Testimonies of Nursing Care after the Atomic Bombing of Nagasaki in 1945 - Matsunari, Yuko; Nakao, Ruiko (Prehospital and disaster medicine, 2013)
To describe the situation with respect to nursing care conducted immediately before and after the atomic bombing of Nagasaki in 1945. Nurses who were registered nursing staff in Nagasaki at the time of the bombing volunteered to participate in this research. Individual interviews were conducted to obtain information concerning the nursing activities in affected areas. The collected information was compared with official documents regarding the atomic bombing of Nagasaki and findings of current studies of disaster situation nursing. Five participants indicated that starting on the day of the bombing, nursing care activities changed from moment to moment according to the condition of radiation victims, the condition of affected areas, and the relief systems in place. Under these conditions, nurses attempted to provide nursing care to victims of the bombing through any means possible. The participants in the present study communicated a single message: that nursing care must be flexible in critical situations. Triage and cooperation with other types of medical professionals were also identified as important factors in nursing care.